Deltopectoral Approach for Arthroplasty After Early Failed Proximal Humerus Fixation Via Deltoid Split Heals Uneventfully: A Case Report. Issue 3 (18th July 2020) - DeBaun, Malcolm R.; Goodnough, L. Henry; Gatewood, Corey; Gardner, Michael J.; Abrams, Geoffrey D.
Abstract : Case: A 57-year-old male carpenter sustained a 2-part displaced proximal humerus fracture of his nondominant arm with varus angulation after a fall down the stairs. Fifteen days postinjury, the patient underwent direct reduction and surgical fixation with an intramedullary cage implant via a deltoid split approach. Nine days postsurgery, the patient presented to the emergency department after another fall with failed fixation. Two weeks after index surgery, he was revised to a reverse total shoulder arthroplasty via a deltopectoral approach and healed both incisions uneventfully. Conclusion: A deltopectoral approach performed acutely after a deltoid split approach for fracture can heal uneventfully.